The German undervaluation regime under Bretton Woods: How Germany became the nightmare of the world economy - Martin Höpner (Max Planck Institute for the Study of Societies, 2019)
Germany is an undervaluation regime, a regime that steers economic behavior towards deterioration of the real exchange rate and thereby towards export surpluses. This regime has brought the eurozone to the brink of collapse. But it is much older than the euro. It was established during the Bretton Woods years and has survived all subsequent European currency orders. The regime operates in two steps: competitive disinflation against trading partners; and resistance against correcting revaluations. The Bretton Woods order provided perfect conditions for the establishment and perpetuation of the regime: it was flexible enough for sufficient macroeconomic policy autonomy to bring about differential inflation rates, and sticky enough to delay and minimize revaluations. – – Deutschland ist ein Unterbewertungsregime: ein Regime, das wirtschaftliches Verhalten in Richtung eines sinkenden realen Wechselkurses und damit der Generierung von Exportüberschüssen lenkt. Das hat die Eurozone an den Rand des Zusammenbruchs geführt. Aber das Regime ist viel älter als der Euro. Es wurde in den Bretton-Woods-Jahren errichtet und überlebte alle nachfolgenden europäischen Währungsordnungen. Das Regime operiert in zwei Schritten: kompetitive Disinflationierung gegenüber den Handelspartnern und Widerstand gegen die Korrektur der entstandenen Wechselkursverzerrungen. Bretton Woods stellte perfekte Bedingungen für die Errichtung und Aufrechterhaltung des Regimes bereit. Denn es war flexibel genug für jene Autonomie der makroökonomischen Politik, mit der sich die Inflation der Handelspartner unterbieten ließ, und gleichzeitig schwerfällig genug für die Verzögerung und Minimierung von Aufwertungen.
hdl:21.11116/0000-0002-EB87-D
Keywords: 300; current account surpluses; exchange rate policy; inflation; political economy; undervaluation; varieties of capitalism; Inflation; Leistungsbilanzüberschüsse; Politische Ökonomie; Spielarten des Kapitalismus; Unterbewertung; Wechselkurspolitik